Dampak Pembelajaran Berbasis Internet Terhadap Kemampuan Bersosial Siswa Kelas X SMK Ibnu Khaldun - Arif Rohman Hakim; Wulandari Wulandari; Ayi Handayani; Indah Purnamasari; Uum Siti Ningrum (Publikasi Indonesia, 2024)
Studying the impact of internet-based learning on students' social skills is important because humans are actually social creatures who need other people no matter what their circumstances. Unfortunately, the impact of internet-based learning on the social skills of students in class The aim of this research is to determine the impact of internet-based learning on the social skills of class X students at Ibnu Khaldun Vocational School for the 2023/2024 academic year. The research method used is descriptive qualitative with data collection techniques through observation, interviews with 7 students, 3 teachers and the school principal as well as documentation. The research subjects were class X students at Ibnu Khaldun Vocational School, Cirebon. The research was carried out for 1 month, namely February 2024. The data collected was then analyzed in depth to determine the research results. The results of the research show that internet-based learning implemented in class able to overcome problems that occur with friends, and direct communication skills worsen, so that students' social interactions can be carried out optimally